A preliminary study on the Islamic creativity practices - Nizah M.A.M.; Ismail A.; Mohamad A.S.; Kandil H.M.T.E.; Atoma P.; Muhammad Mustaqim Mohd.Zarif (Mediterranean Center of Social and Educational Research, 2024)
Indexed by Scopus